Houseboat as a new tourism product in Royal Belum State Park / Rohaslinda Ramele Ramli ... [et al.] - Ramele Ramli, Rohaslinda; Ahmad Kamal, Norashikin; Abdul Adis, Azizi; Amir, Amnorzahira (UiTM Press, 2022)
The houseboat is one of the vessels used to accommodate the users' navigational needs in Belum and Kenyir. It is an alternative to other accommodations for the camping site, resort, and hotel. Houseboats are the largest watercraft; they can be between 60 to 85 feet in length and up to 30 feet in width. Activities such as watching television and karaoke, washing, cooking, and fishing can be carried out on the houseboats. Houseboat can be parked at the jetty or moving around the Royal Belum State Park, and these activities are done on the boats. It mainly accommodates 14 people and usually consists of 4 cabins or rooms. This study aims to overview the houseboat as a new tourism product in Royal Belum State Park by revealing its history and implementation while focusing on its operation and management. In addition, reviews on previous research, field investigation, and interviews with the houseboat operators and Perak State Parks Corporation representatives were conducted. Findings showed that houseboat is a potential accommodation and infrastructure that must be developed and promoted as a tourism product. However, there is a lack of study on the houseboat in Malaysian national and state parks, mainly in Royal Belum State Park, and guidance on how to manage and operate a houseboat to be a successful tourism product that can bring more positive impacts on the economy, society, and environment.